2022
DOI: 10.1038/s41467-022-33575-4
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the structural basis of targeted protein degradation by integrating molecular dynamics simulations with structural mass spectrometry

Abstract: Targeted protein degradation (TPD) is a promising approach in drug discovery for degrading proteins implicated in diseases. A key step in this process is the formation of a ternary complex where a heterobifunctional molecule induces proximity of an E3 ligase to a protein of interest (POI), thus facilitating ubiquitin transfer to the POI. In this work, we characterize 3 steps in the TPD process. (1) We simulate the ternary complex formation of SMARCA2 bromodomain and VHL E3 ligase by combining hydrogen-deuteriu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
92
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 54 publications
(93 citation statements)
references
References 69 publications
1
92
0
Order By: Relevance
“…This has been thoroughly discussed in the review on enzymology of degraders 152 . A few recent studies have used physics modeling 153,154 and ML techniques 155 to predict or rationalize degradability of PROTAC molecules. These studies all point to lysines, especially those that are E2-accesible ubiquitination sites, are indicative of degradation potential.…”
Section: Concluding Discussionmentioning
confidence: 99%
“…This has been thoroughly discussed in the review on enzymology of degraders 152 . A few recent studies have used physics modeling 153,154 and ML techniques 155 to predict or rationalize degradability of PROTAC molecules. These studies all point to lysines, especially those that are E2-accesible ubiquitination sites, are indicative of degradation potential.…”
Section: Concluding Discussionmentioning
confidence: 99%
“…Our model suggests that the optimal range of cooperativity depends on the ubiquitination rate (Figure a). The target in the ternary complexes of different HBF molecules may have different ubiquitination rates because of the difference in their structural ensembles, , which affects the exposure of lysines on the target surface to ubiquitination . If ubiquitination is fast, a transient ternary complex is sufficient for ubiquitination to take place, and fast dissociation of the ternary complexcorresponding to a low cooperativityleads to both high turnover of the HBF molecules and rapid production of free, polyubiquitinated target ready for degradation; in contrast, high cooperativityand thus a very stable ternary complexmay hinder the catalytic turnover and slow down the degradation.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, a recent paper by Eron et al reports that PPIs stabilized by PROTACs can still be very dynamic, and X-ray structures of ternary complexes can also not correspond to a biologically relevant conformation, as they only represent a ‘crystallization snapshot’ of a highly dynamic interaction [ 42 ]. Demonstrating the efficacy of combining in silico methods with experimental data for studying the dynamics of PPIs in PROTACs design, a freshly published work by Dixon et al was able to eventually predict the structural basis of targeted protein degradation [ 43 ]. In this work, the authors showed that productive ternary complexes, modelled in the context of the full Cullin-RING ligase, are characterized by the proximity of lysine residues of the target protein to the E2 ligase.…”
Section: Resultsmentioning
confidence: 99%